Pelatihan Pembuatan Produk Kerajinan Tangan dari Tali Kur pada Masyarakat Binaan Teras Literasi Rumah Kita - Heru Heru; Refi Elfira Yuliani (Universitas Mathla'ul Anwar Banten, 2021)
TRAINING ON MAKING HANDICRAFT PRODUCTS FROM KUR ROPES FOR OUR HOME LITERACY TERRACE ASSISTED COMMUNITIES. Community Service Training on Making Handicraft Products from Cords for the Community Assisted by Teras Literasi Rumah Kita aims to provide participants with an understanding of the prospect of rope crafts, providing skills to participants to make handicrafts made from ropes such as purses and bags. The activities used in this service are in the form of Training and Monitoring. The training was conducted using lecture, demonstration, practice, question and answer, observation and assignment methods. Assignments are given to all participants to complete the embroidery of a purse or bag. Participants can work at home or while attending the recitation at the Literacy Teras Rumah Kita. Monitoring is carried out at every recitation activity of the inmates, with literacy terraces taking place. At the time of the recitation, the participants brought the embroidery of the rope, and it would be completed after doing the recitation. After the recitation, monitoring was carried out on the participants' tasks in embroidering the string. If it is in embroidery, then the embroidery will be removed to the wrong point, but there are no errors. Participants can continue the embroidery until the product is finished. The output of this activity is craft products made from ropes in the form of wallets and bags.